2015
DOI: 10.1007/s11270-015-2343-4
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Deposition of Pesticides in a Canadian City: Part 1. Glyphosate and Other Agricultural Pesticides

Abstract: Winnipeg is a city in the Canadian Prairies with a population of about 600,000. Like many other cities and towns in this region of Canada, the city is surrounded by agriculture. Weekly bulk deposition samples were collected from May to September in 2010 and 2011 and analyzed for forty-three pesticides used in Prairie agriculture. Fourteen herbicides, five herbicide metabolites, two insecticides and two fungicides were detected with 98.5% of the samples containing chemical mixtures. Glyphosate is the most widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Therefore, the ratio should consider not only the amount applied but also the amount accumulated from previous treatments. Recent experimental and monitoring studies confirm wind-driven transport of glyphosate and AMPA (Bento et al, 2017;Farenhorst et al, 2015;Lamprea and Ruban, 2011;Quaghebeur et al, 2004). Bento et al (2017) demonstrated in a wind tunnel experiment that contents of AMPA and especially of glyphosate were particularly high (respectively N 0.6 and N 15 μg g −1 ) in the finest soil particle fractions (b 10 μm), which can be inhaled by humans directly.…”
Section: Off-site Transport By Wind and Water Erosionmentioning
confidence: 79%
“…Therefore, the ratio should consider not only the amount applied but also the amount accumulated from previous treatments. Recent experimental and monitoring studies confirm wind-driven transport of glyphosate and AMPA (Bento et al, 2017;Farenhorst et al, 2015;Lamprea and Ruban, 2011;Quaghebeur et al, 2004). Bento et al (2017) demonstrated in a wind tunnel experiment that contents of AMPA and especially of glyphosate were particularly high (respectively N 0.6 and N 15 μg g −1 ) in the finest soil particle fractions (b 10 μm), which can be inhaled by humans directly.…”
Section: Off-site Transport By Wind and Water Erosionmentioning
confidence: 79%
“…Chang et al (2011) observed maximum glyphosate concentration of 2.5 ng/mL in rain water when rainfall follows the application period, while AMPA reached 2 ng/mL in rain water. Farenhorst et al (2015) detected Table 1 Physicochemical soil properties. Particle size distribution, % organic carbon content (OC%) and pH along the soil profile.…”
Section: Glyphosate and Ampa Content In Soil Control Area (Ca S )mentioning
confidence: 99%
“…Since neither of these herbicides was applied to crops on organic farms, their low detection frequency in these wetlands could result from short-to long-range atmospheric transport inputs. In agreement with an atmospheric transport mechanism, Majewski et al (2014), Messing et al (2011), Chang et al (2011), and Farenhorst et al (2015 have reported glyphosate and AMPA in rain. However, because glyphosate exists as a zwitterion, it is strongly sorbed to soil and plant surfaces.…”
Section: Discussionmentioning
confidence: 99%